Knee Injuries in Volleyball Players: A Review Report - Sahar Farohki; Ali Fatahi (Biyumikānīk-i varzishī)
Objective Knee injuries, both in terms of severity and frequency, are among the most significant injuries in the sport of volleyball. The objective of this research was to review the relevant literature on knee injuries in volleyball. Methods This study was a library-based review, examining articles written in Persian and English published between 2000 and 2023. Articles were sourced from reputable domestic and international databases. Out of a total of 769 extracted articles, 104 were selected and thoroughly reviewed based on predefined criteria. Results The findings indicated that knee injuries are the second most common type of injury in volleyball. Among different age and gender groups, the highest injury rate was observed in semi-professional female volleyball players, with a rate of 7.7 injuries per 1000 athlete-hours. Ligament injuries were the most common type of knee injury reported in volleyball. The primary contributing factor to these injuries was the force applied to the lower limbs, particularly in unfavorable body positions during initial impact. Preventive exercises, including strength training, core stability, neuromuscular, and combined exercises, were recommended in the literature. Conclusion This study highlights the importance of addressing knee injuries in volleyball, particularly among female athletes. Emphasizing balanced jumping and landing techniques, along with a focus on effective preventive exercises, such as strength training, core stability, and neuromuscular exercises, is recommended based on the relevant research literature.